Teknologi Edible Coating dari Lilin Lebah (Beeswax) dan Kolang kaling (Arenga pinata Merr.);Terhadap Mutu Buah Tomat (Lycopersicum esculentum L.) - Syahrozy Erwin; Noor Khamidah; Untung Santoso (Universitas Lambung Mangkurat, 2022)
Tomato (lycopersicum esculentum L.) is a fruit that is quite popular and has many uses. In addition to the abundant production of tomatoes, tomatoes have a relatively short shelf life and are easily damaged both mechanically and physiologically. In maintaining the quality of tomatoes so that they are durable and reach the hands of consumers, it is necessary to have good post-harvest handling. Edible coating is one of technology that can be used to maintain fruit quality. Beeswax and Kolang Kaling (Arenga pinata Merr.) are materials that can be used as edible coatings. This study aims to determine the effect of the edible coating of beeswax and kolang kaling in maintaining the quality of tomatoes. This research was conducted at the Production Laboratory and Integrated Laboratory of the Agroecotechnology Department, Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru from November to December 2020. The method used in this study was (CRD), a completely randomized design with 1 factor namely, edible coating material used. There were 3 treatments of edible caoting material in this study, control or without coating agent (EC0), 6% beeswax emulsion (EC1) and 10% kolang kaling emulsion (EC2) and repeated 6 replications. The observations or benchmarks in this study were fruit color, fruit texture, fruit taste and weight loss of tomatoes which were observed for 12 days. The results of this study indicate that the provision of edible caoting has a effect on the quality of tomatoes. based on the organoleptic test, 6% beeswax treatment was the best treatment in this study to maintain the quality of tomatoes during the observation. Based on the analysis of various treatments, 6% beeswax had a very significant effect on the weight loss of tomatoes on the 8th and 12th days